Effects of Ayahuasca on Personality: Results of Two Randomized, Placebo-Controlled Trials in Healthy Volunteers - Mendes Rocha, Juliana; Rossi, Giordano Novak; Osório, Flávia L.; Bouso Saiz, José Carlos; Silveira, Gabriela De Oliveira; Yonamine, Mauricio; Crevelin, Eduardo José; Queiroz, Maria Eugênia; Cecílio Hallak, Jaime E.; Dos Santos, Rafael Guimarães (Frontiers in Psychiatry, 2021)
Rationale: Previous studies with the serotonergic hallucinogens LSD and psilocybin showed that these drugs induced changes in personality traits, such as increases in Openness. However, results are inconsistent, and the effects of ayahuasca on personality were never investigated in a controlled trial. Objectives: To assess the effects of ayahuasca on personality in two randomized, placebo-controlled trials in healthy volunteers. Methods: Data from two parallel-group, randomized, placebo-controlled trials in healthy volunteers were included. In the first trial, 15 volunteers ingested ayahuasca or placebo, while in the second trial 15 volunteers received placebo+ayahuasca or cannabidiol (CBD)+ayahuasca. Personality was assessed with the NEO-Five Factor Inventory (NEO-FFI) at baseline and 21 days post-treatment. Results: There were significant differences between groups in baseline Openness scores, but not on day 21. A significant increase in Openness scores was observed in the placebo+ayahuasca group in study 2. No other within-group differences were observed for any other domain. Conclusions: Ayahuasca produced inconsistent effects on personality since it induced significant increase in Openness 21 days post-drug intake only in one of the trials. The absence of significant differences in the other ayahuasca groups could be due to small sample sizes and baseline differences among groups. The effects of ayahuasca and other serotonergic hallucinogens on personality should be further investigated in clinical samples.